Medical student satisfaction and confidence in simulation-based learning in Rwanda – Pre and post-simulation survey research - Turatsinze, Simeon (Afr J Emerg Med, 2020)
INTRODUCTION: Simulation-based learning (SBL) has been shown to effectively improve medical knowledge, procedural proficiency, comfort with undertaking taught tasks, inter-professional communication, teamwork and teaching skills. This study aimed to evaluate Rwandan medical students' attitudes, satisfaction and confidence level with SBL. METHODS: Fifth year medical students at the University of Rwanda were given a short course on paediatric acute care using simulation. The simulation sessions were locally developed cases based on the pRRAPID materials, developed at the University of Leeds (UK). Equipment included low fidelity infant mannequins, basic airway devices, IV access, and monitoring. A four-part, Likert-scale questionnaire was distributed to medical students before and after their four-week simulation program. RESULTS: 57 pre-simulation and 49 post-simulation questionnaires were completed. Confidence in skills increased in all fifteen domains of the questionnaire with the total skill confidence score rising from 44.0 (±12.3) to 56.2 (±8.8) after the simulation-based intervention (p < 0.001). Satisfaction and attitudes towards simulation-based learning in this setting were very positive. CONCLUSION: The simulation-based intervention was well received by students in this setting. Satisfaction was high and the simulation exercise increased the students' confidence. Previous research has demonstrated that SBL is effective and the results of this study now demonstrate that it is well received in our setting. As we move from knowledge-based education to a competency-based education culture, faculties in this setting should invest in providing SBL opportunities throughout the medical school curriculum.